Chile : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Chile. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that GDP growth in Chile has been weak, with activity slowing in October. However, conditions are in place for the economy to recover. After expanding by a moderate 1.7 percent in 2016, growth is forecast to increase to 2 percent in 2017. Faster growth in main regional partners and more stable copper prices are expected to lift exports and investment. The recovery is, however, projected to be gradual, held back by slow wage and job growth and still low business confidence. The financial sector appears healthy. Banks' profitability is declining, but capital buffers are adequate and nonperforming loan rates are low.